2013
DOI: 10.1103/physrevlett.111.140401
|View full text |Cite
|
Sign up to set email alerts
|

Time Scales in the Approach to Equilibrium of Macroscopic Quantum Systems

Abstract: We prove two theorems concerning the time evolution in general isolated quantum systems. The theorems are relevant to the issue of the time scale in the approach to equilibrium. The first theorem shows that there can be pathological situations in which the relaxation takes an extraordinarily long time, while the second theorem shows that one can always choose an equilibrium subspace the relaxation to which requires only a short time for any initial state. The recent renewed interest in the foundation of quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
149
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(153 citation statements)
references
References 24 publications
2
149
0
2
Order By: Relevance
“…Since the mid2000s there has been increasing research activities in the field of "equilibration" and "thermalization" with respect to closed quantum systems, although the latter mechanisms are traditionally associated with stochastic processes. Most of these research activities have focused on the remarkable fact that after some, possibly very long, time [3][4][5], the behavior of many observables is very well be practically indistinguishable from standard phenomenological equilibrium behavior, despite the fact that the Schrödinger equation does not feature any attractive fixed point. Some of these attempts follow concepts of pure state quantum statistical mechanics [6,7], typicality [8][9][10], or eigenstate thermalization hypothesis [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Since the mid2000s there has been increasing research activities in the field of "equilibration" and "thermalization" with respect to closed quantum systems, although the latter mechanisms are traditionally associated with stochastic processes. Most of these research activities have focused on the remarkable fact that after some, possibly very long, time [3][4][5], the behavior of many observables is very well be practically indistinguishable from standard phenomenological equilibrium behavior, despite the fact that the Schrödinger equation does not feature any attractive fixed point. Some of these attempts follow concepts of pure state quantum statistical mechanics [6,7], typicality [8][9][10], or eigenstate thermalization hypothesis [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Modern researches has revealed that even a pure quantum state, described by a single wave function without any genuine thermal fluctuation, can relax to macroscopic thermal equilibrium by a reversible unitary evolution [1][2][3][4][5][6][7][8][9][10][11]. Thermalization of isolated quantum systems, which is relevant to the zeroth law of thermodynamics, is now a very active area of researches in theory [1][2][3][4][5][6], numerics [10][11][12][13][14][15][16], and experiments [17][18][19][20][21][22][23]. Especially, the concepts of typicality [9,[24][25][26] and the eigenstate thermalization hypothesis (ETH) [10][11][12][27][28][29][30][31][32][33][34][35]…”
mentioning
confidence: 99%
“…Although the microscopic laws of physics do not prefer a particular direction of time, the macroscopic world exhibits inevitable irreversibility represented by the second law of thermodynamics. Modern researches has revealed that even a pure quantum state, described by a single wave function without any genuine thermal fluctuation, can relax to macroscopic thermal equilibrium by a reversible unitary evolution [1][2][3][4][5][6][7][8][9][10][11]. Thermalization of isolated quantum systems, which is relevant to the zeroth law of thermodynamics, is now a very active area of researches in theory [1-6], numerics [10][11][12][13][14][15][16], and experiments [17][18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…In particular, for the experimentally accessible case i) β∆E ≫ 1, the relaxation time is the same order as the so-called Boltzmann time T 1 = β , which is compatible to Refs. [12,13]. Further analysis of relaxation time demands careful choice of the observables and Hamiltonian, and remains as no-man's land.…”
Section: Discussionmentioning
confidence: 99%
“…The relaxation time in the present paper is compatible to Refs. [12,13]. It provides a first step to analyze the generic relaxation time.…”
Section: Introductionmentioning
confidence: 99%